1984
DOI: 10.1016/s0735-1097(84)80289-2
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic function in hypertension: relation to left ventricular mass and systolic function

Abstract: Initial studies of diastolic cardiac function in hypertension demonstrated that slowing of the maximal rate of left ventricular filling occurred before alterations in either ejection fraction or cardiac output. The present study was undertaken to determine: 1) the relation between hypertension, increased left ventricular mass and impaired left ventricular filling, and 2) the correlation between abnormalities in left ventricular diastolic function and its systolic performance. Eleven normal subjects (Group 1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
89
3
5

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(106 citation statements)
references
References 16 publications
8
89
3
5
Order By: Relevance
“…It is well known that diastolic function is influenced by several factors, such as age, preload, LV mass, and BP load. 33,38,39 However, the difference found between Fϩ and FϪ groups cannot be ascribed to differences between groups in terms of age, BMI, or 24-hour BP profile, as underlined above, or to differences in preload or LV hypertrophy, in view of the fact that LV end-diastolic diameter, index of preload, and LV mass index were similar between the 2 lean groups and between the 2 obese groups. From multiple regression analysis, in addition to LV mass index and BMI, stimulated insulinemia and genetic predisposition to hypertension were also significant predictors of LV diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that diastolic function is influenced by several factors, such as age, preload, LV mass, and BP load. 33,38,39 However, the difference found between Fϩ and FϪ groups cannot be ascribed to differences between groups in terms of age, BMI, or 24-hour BP profile, as underlined above, or to differences in preload or LV hypertrophy, in view of the fact that LV end-diastolic diameter, index of preload, and LV mass index were similar between the 2 lean groups and between the 2 obese groups. From multiple regression analysis, in addition to LV mass index and BMI, stimulated insulinemia and genetic predisposition to hypertension were also significant predictors of LV diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 94%
“…Studies conducted on hypertensive patients demonstrated a direct relationship between the degree of LVH and impairment of diastolic filling. 29) Tsioufis, et al 12) demonstrated that compared to their counterparts without EBPR, hypertensives with EBPR were characterized by more pronounced LV diastolic dysfunction assessed by TDI. In our HTN subjects, however, no statistically significant difference was noticed in LV diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…15 Fouad et al 16 considers as dynamic factors those conditions which, due to their functional character, may be modified and controlled in a short period of time. Among these factors, afterload, abnormal kinetics of calcium-associated with the development of LVH-general or regional myocardial ischaemia and sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%